Energy-Dominated Local Carbon Emissions in Beijing 2007: Inventory and Input-Output Analysis. (24th October 2012) - Guo, Shan; Liu, J. B.; Shao, Ling; Li, J. S.; An, Y. R.
Abstract : For greenhouse gas (GHG) emissions by Beijing economy 2007, a concrete emission inventory covering carbon dioxide (CO2 ), methane (CH4 ), and nitrous oxide (N2 O) is presented and associated with an input-output analysis to reveal the local GHG embodiment in final demand and trade without regard to imported emissions. The total direct GHG emissions amount to 1.06 E + 08 t CO2 -eq, of which energy-related CO2 emissions comprise 90.49%, non-energy-related CO2 emissions 6.35%, CH4 emissions 2.33%, and N2 O emissions 0.83%, respectively. In terms of energy-related CO2 emissions, the largest source is coal with a percentage of 53.08%, followed by coke with 10.75% and kerosene with 8.44%. Sector 26 ( Construction Industry ) holds the top local emissions embodied in final demand of 1.86 E + 07 t CO2 -eq due to its considerable capital, followed by energy-intensive Sectors 27 ( Transport and Storage ) and 14 ( Smelting and Pressing of Ferrous and Nonferrous Metals ). The GHG emissions embodied in Beijing's exports are 4.90 E + 07 t CO2 -eq, accounting for 46.01% of the total emissions embodied in final demand. The sound scientific database totally based on local emissions is an important basis to make effective environment and energy policies for local decision makers.